Labour Market Participation of the Elderly (The Pakistan Development Review, 2000)
Generally ageing of population is defined as the relative increase in the number of elderly. This process is the result of declining fertility and increasing life expectancy of elderly population. In today’s Pakistan, fertility has started declining and life expectancy of elderlies has been increasing and it is expected that in future both these processes will gain momentum, resulting into many fold increase in the population of elderly people [Afzal (1999); Sathar and Casterline (1998)]. These developments are expected to have adverse effects on Pakistan’s economy as support and welfare of elderly people will require additional allocation of resources. That is more so because traditionally welfare and socio-economic needs of elderly people remained the responsibility of their children especially the sons. However, the traditional extended/joint family system is fast breaking down and nuclear type of family set up is becoming more common rendering the elderly people helpless [Ali (2000)]. Moreover, in view of an increase in the incidence of poverty in Pakistan, intra-house resource distribution is also becoming scarce leading to a scenario where only productive members are the chief beneficiaries [Qureshi and Arif, (2001)].